2015
DOI: 10.4028/www.scientific.net/amr.1088.514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Composition on the Fracture Toughness of Cortical Bone

Abstract: This study was aimed at investigating the effect of the bone compositions on the fracture toughness of bovine cortical bone. A series of the SENB bovine cortical bone specimens were tested to assess the fracture toughness. Dual energy X-ray absorptiometry (DEXA) was applied to determine the mineral content of each bovine cortical specimen and hence the porosity and bone mineral fraction were measured. Current results indicate that the mean value fracture toughness is 9.37 MNm3/2. Moreover, the fracture toughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…31 Numerous experimental studies determined the effect of several parameters, that is, sugar, age, hydration, mineralization, preservative method, fatigue loading, strain rate, porosity, anisotropy, demineralization, deproteinization, type of specimen, indentation, shear deformation, bone composition, etc., on fracture parameters of cortical bone. 2123,3264 Many researchers have validated their numerically predicted results with the experimental analysis as well. 22,40,42,47,51,62…”
Section: Experimental and Numerical Analysis Of Cortical Bone Fractur...mentioning
confidence: 91%
See 1 more Smart Citation
“…31 Numerous experimental studies determined the effect of several parameters, that is, sugar, age, hydration, mineralization, preservative method, fatigue loading, strain rate, porosity, anisotropy, demineralization, deproteinization, type of specimen, indentation, shear deformation, bone composition, etc., on fracture parameters of cortical bone. 2123,3264 Many researchers have validated their numerically predicted results with the experimental analysis as well. 22,40,42,47,51,62…”
Section: Experimental and Numerical Analysis Of Cortical Bone Fractur...mentioning
confidence: 91%
“…All the mentioned studies in this review have considered wet bone. Therefore, studies on bovine and human bone have indicated the increment in K C of cortical bone with increasing dry and wet density 23,26,40,41,50,61,108,126128 and decrease in K C with increasing mineral content or porosity. 110,111,129 Mineralization and moisture are the foremost aspects affecting the mechanical response of the compact bone.…”
Section: Experimental and Numerical Analysis Of Cortical Bone Fracture Parametersmentioning
confidence: 99%